2006
DOI: 10.1513/pats.200512-125sf
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Smokers with stable chronic obstructive pulmonary disease have a chronic inflammation of the entire tracheobronchial tree characterized by an increased number of macrophages and CD8 T lymphocytes in the airway wall and of neutrophils in the airway lumen. Exacerbations of chronic obstructive pulmonary disease are considered to reflect worsening of the underlying chronic inflammation of the airways, caused mainly by viral and bacterial infections and air pollution. During exacerbations, the inflammatory cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 97 publications
4
102
2
2
Order By: Relevance
“…Moreover, these findings provide a biological hypothesis for the epidemiological relationship between ozone and increased pulmonary morbidity and mortality. Loss of lung function in chronic obstructive pulmonary disease is related to exposure to environmental air pollutants (34,35) and frequency of exacerbations (36). Our observations support that exposure to ozone can significantly enhance both lung injury and macrophage apoptosis after exposure to inhaled endotoxin.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, these findings provide a biological hypothesis for the epidemiological relationship between ozone and increased pulmonary morbidity and mortality. Loss of lung function in chronic obstructive pulmonary disease is related to exposure to environmental air pollutants (34,35) and frequency of exacerbations (36). Our observations support that exposure to ozone can significantly enhance both lung injury and macrophage apoptosis after exposure to inhaled endotoxin.…”
Section: Discussionsupporting
confidence: 70%
“…The 'triad' of mucus gland hyperplasia, mucus retention and surfactant dysfunction produces dire consequences on the pulmonary gas-exchange. The inflammatory response has prompted some researchers to propose the 'inflammatory/anti-inflammatory' hypothesis for COPD, that also provides a sound basis for the use of anti-inflammatory drugs in the disease [50].…”
Section: The Pathobiology Of Copdmentioning
confidence: 99%
“…It was reported that the airway epithelium is an abundant source of chemokines/ cytokines which attract both macrophages and neutrophils [51]. Activated neutrophils can result in wide spread inflammation of the lung tissue, destruction of basement membrane of alveolar capillary membrane and increase of its permeability.…”
Section: Discussionmentioning
confidence: 99%